SiC-W2B5 / C composite material and preparation method thereof
SiC is generated by reacting Si powder with C phase, and SiC is used as a high-temperature liquid phase to solve the problems of low activity and high density in the sintering process of W2B5/C composite materials, and the SiC-W2B5/C composite materials with high density and excellent mechanical properties are achieved. It is suitable for the hot bending glass industry and sintering and storage of cemented carbide tools.
Patent Information
- Application Number
- CN202510103910.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sintering process of W2B5/C composites has problems with low sintering activity and high density, resulting in limited material performance and increased energy consumption.
SiC is generated by reacting Si powder with C phase, and SiC is used as a high-temperature liquid phase during the sintering process to reduce the sintering temperature and increase the density. At the same time, the SiC phase generated by the reaction enhances the interface binding force and improves the mechanical properties.
It has achieved high density and excellent mechanical properties of composite materials, reduced density and energy consumption, and expanded its application in the hot bending glass industry and cemented carbide tool sintering and other fields.
Smart Images

Figure CN119528574A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-based composite materials, and in particular relates to a SiC-W2B5 / C composite material and a preparation method thereof. Background Art
[0002] W2B5 / C composite materials have been widely used in the engineering field due to their excellent properties such as high strength, high thermal stability and good conductivity. For example, they are used as heating materials, electronic materials, high-temperature heat exchangers and other materials, and are used in mold manufacturing and other processes in the hot-bending glass industry.
[0003] However, the current sintering process of W2B5 / C composite materials has many unsatisfactory aspects. For W2B5 / C composite materials with high carbon content, their sintering activity is usually low, resulting in poor plasticity during the sintering process. This not only limits the performance of the material, but also increases the resistance during the densification process, making it difficult to prepare high-density composite materials. At the same time, when the W2B5 content increases, although it can make the composite material reach the optimal performance state, it also brings the problem of excessive density. In application scenarios such as mold manufacturing in the hot-bent glass industry, higher density means that greater mechanical transmission power is required, which in turn leads to a significant increase in energy consumption.
[0004] In order to improve the performance of W2B5 / C composite materials, the industry usually adopts the method of adding a second phase to improve its sintering behavior and mechanical properties, in order to obtain a composite material with superior performance and high practicality. The second phase can not only enhance the activation and volume diffusion of the grain boundary, thereby increasing the density of the composite material and further optimizing its overall performance. At the same time, according to the dispersion strengthening theory of composite materials, when there are high-strength second-phase ceramic particles at the crack, it will induce crack deflection, bifurcation or pinning effects, thereby enhancing the ability of the matrix to resist fracture and improving the strength of the material. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a SiC-W2B5 / C composite material, which utilizes Si powder to react with C phase to generate SiC. During the sintering process, Si can not only serve as a high-temperature liquid phase, thereby reducing the sintering temperature and improving the density of the composite material; at the same time, the SiC phase generated by the reaction enhances the interfacial bonding force, thereby improving the mechanical properties of the composite material.
[0006] Another object of the present invention is to provide a method for preparing a SiC-W2B5 / C composite material, which has a simple process and is easy to control.
[0007] The preparation method of the SiC-W2B5 / C composite material of the present invention comprises the following steps: (1) Mix tungsten carbide, boron carbide, calcined petroleum coke, silicon powder and ball milling dispersant, place in a ball mill for ball milling, dry and sieve after ball milling to obtain raw material powder; (2) The raw material powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 5-15 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 5-30 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0008] The step-by-step reaction equation is as follows: Si+B4C→SiC+4[B]; Si+C→SiC; 2WC+5[B]→W2B5+2C.
[0009] The overall reaction equation is as follows: 8WC+5B4C→4W2B5+13C; Si+C→SiC.
[0010] The molar ratio of the tungsten carbide, boron carbide, calcined petroleum coke and silicon powder is 1: (0.6-0.7): (10-70): (1-4).
[0011] The density of the tungsten carbide is 15.7 g / cm 3 , the density of boron carbide is 2.5g / cm 3 The density of calcined petroleum coke is 2.2g / cm 3 , the density of silicon powder is 2.3g / cm 3 ; The density of SiC phase in SiC-W2B5 / C composite material is 3.2g / cm 3 The density of W2B5 phase is 11.2 g / cm 3 , the density of phase C is 2.2 g / cm 3 .
[0012] The ball-to-material ratio of the ball mill is (1~2):1.
[0013] The ball milling dispersant is anhydrous ethanol, and the ratio of the amount of the ball milling dispersant to the total amount of tungsten carbide, boron carbide, calcined petroleum coke and silicon powder is (100-150): 100 mL / g.
[0014] The ball mill has a rotation speed of 80-120 r / min and a milling time of 12-24 h.
[0015] The temperature of the hot pressing reaction sintering is 1500-1700°C and the pressure is 10-20MPa.
[0016] The hot pressing reaction sintering time is 0.5~1h.
[0017] The SiC-W2B5 / C composite material is prepared by the above-mentioned method for preparing the SiC-W2B5 / C composite material.
[0018] The reaction mechanism of the present invention is as follows: Since the radius of B atoms is smaller than the radius of W atoms, during the reaction, the B atoms in B4C diffuse to the W atoms in WC, and react at the interface to generate W2B5. According to the same WB phase diagram and Gibbs free energy calculation, the reaction temperature needs to be above 1800°C. Due to the presence of Si in the reaction system, the diffusion rate of B is relatively high, which reduces the generation temperature of W2B5. When the temperature reaches above 1450°C, silicon melts into a liquid phase, and can react with B4C at this temperature to generate SiC and 4 B atoms. The B atoms with light weight and small atomic radius encounter less diffusion resistance and a large diffusion rate, and can diffuse into WC. With the increase of liquid phase Si, the diffusion coefficient of B atoms increases sharply, which promotes the diffusion of active B atoms through the WB layer into WC. When the penetration amount of B atoms in WC exceeds the limit solid solubility, a substitution reaction occurs between B atoms and WC to generate W2B5. The consumption of active B atoms can promote the further decomposition of B4C, thereby further promoting the reaction.
[0019] The power of the sintering process of the present invention mainly comes from the surface tension and interfacial tension of liquid Si. The whole process can be roughly divided into the following stages: (1) Rearrangement stage of liquid Si and raw material particles. Under the action of the surface tension of liquid Si, capillary force will be formed in the wetting pores between the solid B4C and WC particles, accompanied by the viscous flow of the liquid phase. These forces work together to accelerate the movement and rearrangement of the solid particles in the system to achieve the effect of sintering densification. Liquid Si wets the solid particles and penetrates into their gaps, causing the solid / gas interface in the reaction system to gradually disappear. The stress on the pores varies with the size of the pores, so the pressure difference between large and small pores will drive the liquid Si to flow between these pores. Under the action of surface tension, the liquid Si that penetrates into the gaps between the solid particles will generate a force that accelerates the solid particles to move closer to each other. Due to the differences in size and surface shape of the solid particles in the reaction system, the curvature radius of the liquid Si on the concave surface of the particles is different, resulting in unequal capillary forces and their components acting on the particle surface and in all directions. These forces jointly drive the movement of the reaction particles in the liquid Si and the rearrangement of the particles, thereby promoting the formation of W2B5.
[0020] (2) Solid phase dissolution and reprecipitation stage. The B atoms on the surface of the solid phase B4C particles will gradually dissolve in the liquid phase Si to form a Si-BC solid solution phase. For B4C particles, the liquid phase Si has a large saturated solubility. The parts with higher surface activity, especially the parts with larger curvature, will be dissolved first, which makes the particle surface gradually tend to be flat and smooth, and present an approximate spherical shape. As the dissolution proceeds, a part of the supersaturated atoms in the liquid phase Si will precipitate in the form of SiC on the surface of the large B4C particles. This is the process of solid phase dissolution and reprecipitation, that is, the reaction process is accelerated by the material migration process of the liquid phase Si. The process of dissolution and reprecipitation makes the appearance of the large particles of the reactants gradually tend to be spherical, and the small particles are reduced or disappear. At the same time, the matrix particles achieve a more compact stacking state through shape adaptation, thereby promoting the densification of the composite material.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes Si powder to play the role of high-temperature liquid phase during the sintering process. The presence of liquid phase Si not only accelerates the rearrangement of the reactant phase, but also promotes the dissolution and reprecipitation process of B4C and WC, reduces the sintering temperature, greatly optimizes the microstructure of the composite material, makes the particle distribution more uniform, and significantly reduces the porosity, thereby greatly improving the densification degree of the composite material; (2) The SiC phase generated by the reaction is located between the C phase and the W2B5 phase, forming an effective interface reinforcement phase. The high hardness and high strength characteristics of SiC significantly improve the interface bonding force of the composite material, enhance the ability of the matrix to resist fracture, and improve the overall mechanical properties of the composite material, so that the composite material can still maintain good performance under high temperature and high stress environment; (3) The SiC-W2B5 / C composite material described in the present invention is a low-density and high-strength material compared to the W2B5 / C composite material. It reduces the density and mechanical loss in the actual application process while maintaining the performance of the W2B5 / C composite material. It is particularly suitable for the hot bending mold industry and the cemented carbide tool sintering container industry; (4) The preparation method of the SiC-W2B5 / C composite material described in the present invention has a simple process, is easy to control, has a wide source of raw materials, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Example 1 (×5000 times); Figure 2 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 1 (×5000 times); Figure 3Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Example 2 (×5000 times); Figure 4 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 2 (×5000 times); Figure 5 Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Example 3 (×5000 times); Figure 6 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 3 (×5000 times); Figure 7 Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Example 4 (×5000 times); Figure 8 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 4 (×5000 times); Fig. 9 Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Example 5 (×5000 times); Fig.10 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 5 (×5000 times); Fig.11 Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Example 6 (×5000); Fig.12 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 6 (×5000); Fig.13 Surface electron microscopy image of the SiC-W2B5 / C composite material prepared in Comparative Example 1 (×5000 times); Fig.14 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Comparative Example 1 (×5000 times); Fig.15 Surface electron microscopy image of the TiC-W2B5 / C composite material prepared in Comparative Example 2 (×5000 times); Fig.16 This is a cross-sectional electron micrograph of the TiC-W2B5 / C composite material prepared in Comparative Example 2 (×5000 times); Fig.17 Surface electron microscopy image of the MoC-W2B5 / C composite material prepared in Comparative Example 3 (×5000 times); Fig.18 This is a cross-sectional electron micrograph of the MoC-W2B5 / C composite material prepared in Comparative Example 3 (×5000 times); Fig.19 Surface electron microscopy image of the MoC-SiC-W2B5 / C composite material prepared in Comparative Example 4 (×5000 times); Fig. 20 This is a cross-sectional electron micrograph of the MoC-SiC-W2B5 / C composite material prepared in Comparative Example 4 (×5000 times); Fig.21 This is a surface electron microscope image of the W2B5 / C composite material prepared in Comparative Example 5 (×5000); Fig. 22 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Comparative Example 5 (×5000 times); DETAILED DESCRIPTION The present invention will be further described below with reference to the embodiments.
[0023] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.
[0024] Example 1 The preparation method of the SiC-W2B5 / C composite material comprises the following steps: (1) 18.3 g of tungsten carbide (particle size 4±1 μm), 3.3 g of boron carbide (particle size 4±1 μm), 74.2 g of calcined petroleum coke (particle size 15±5 μm), 4.2 g of silicon powder (particle size 4±1 μm) and 150 mL of anhydrous ethanol were mixed and placed in a ball mill for ball milling at a ball-to-material ratio of 1:1 and a ball milling speed of 80 r / min for 24 h. After ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a raw material powder; (2) The raw material powder is placed in a graphite mold and hot-pressed in a sintering furnace. The temperature of the hot-pressing reaction sintering is 1700°C, the pressure is 20 MPa, and the time is 1 h. After the sintering is completed, the powder is cooled and taken out of the furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 5 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 5 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0025] Figure 1 This is the surface electron microscope image of the SiC-W2B5 / C composite material prepared in Example 1. Figure 1 It can be seen that when the content of W2B5 in the composite material is 5 vol.% and the content of SiC is 5 vol.%, the composite material has fewer pores on the surface and a high degree of density. The increase in densification mainly comes from the liquid phase sintering of Si powder during the hot pressing sintering process at high temperature, which causes plastic flow between particles and accelerates rearrangement. However, due to the low Si content and the small amount of liquid phase components, pores still exist on the surface.
[0026] Figure 2 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 1. Figure 2 It can be seen that with the introduction of SiC ceramic phase, there are fewer pores at the fracture of the composite material, the boundaries between the carbon phase particles are blurred, the matrix is bonded into a whole piece, a cleavage section appears, and a good interface bonding has been formed between the ceramic phase and the carbon phase.
[0027] Example 2 The preparation method of the SiC-W2B5 / C composite material comprises the following steps: (1) 18.1 g of tungsten carbide (particle size 4±1 μm), 3.2 g of boron carbide (particle size 4±1 μm), 70.5 g of calcined petroleum coke (particle size 15±5 μm), 8.2 g of silicon powder (particle size 4±1 μm) and 150 mL of anhydrous ethanol were mixed and placed in a ball mill for ball milling at a ball-to-material ratio of 2:1 and a ball milling speed of 100 r / min for 18 h. After ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a raw material powder; (2) The raw material powder is placed in a graphite mold and hot-pressed in a sintering furnace for sintering at a temperature of 1700°C, a pressure of 15 MPa, and a time of 1 h. After sintering, the powder is cooled and taken out of the furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 5 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 10 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0028] Figure 3 This is the surface electron microscope image of the SiC-W2B5 / C composite material prepared in Example 2. Figure 3 It can be seen that when the content of W2B5 in the composite material is 5 vol.%, and the content of SiC is 10 vol.%, the pores on the surface of the composite material are reduced. This is because SiC and W2B5 particles are attached to the surface of the carbon phase matrix, and are arranged as the carbon phase deflects and embedded between the layers, which is conducive to the plastic flow deformation of the matrix carbon phase, and the large pores become small pores.
[0029] Figure 4 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 2. Figure 4 It can be seen that plastic deformation occurs between the carbon phase and the ceramic phase, the particles are evenly distributed, the microstructure is uniform and dense, the particles fit more closely, filling the gaps between the matrix layers and improving the strength.
[0030] Example 3 The preparation method of the SiC-W2B5 / C composite material comprises the following steps: (1) 30.3 g of tungsten carbide (particle size 4±1 μm), 5.4 g of boron carbide (particle size 4±1 μm), 56.9 g of calcined petroleum coke (particle size 15±5 μm), 7.4 g of silicon powder (particle size 4±1 μm) and 100 mL of anhydrous ethanol were mixed and placed in a ball mill for ball milling at a ball-to-material ratio of 1:1, a ball milling speed of 120 r / min, and a time of 12 h. After ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a raw material powder; (2) The raw material powder is placed in a graphite mold and hot-pressed in a sintering furnace for sintering at a temperature of 1600°C, a pressure of 20 MPa and a time of 1 h. After sintering, the powder is cooled and taken out of the furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 10 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 10 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0031] Figure 5 This is the surface electron microscope image of the SiC-W2B5 / C composite material prepared in Example 3. Figure 5 It can be seen that when the content of W2B5 in the composite material is 10 vol.% and the content of SiC is 10 vol.%, the adhesion of the ceramic phase becomes stronger and stronger, the pores become smaller and smaller, the mutual spreading and infiltration effect of the carbon phase is better, which is more conducive to the sintering and densification of the material, making the organizational structure of the composite material more uniform and dense.
[0032] Figure 6 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 3. Figure 6 It can be seen that the ceramic phase of the composite material is attached to the surface of the carbon phase, deflected and rearranged, and plays a supporting and bridging role between the matrix layers. The matrix materials of the composite material are tightly combined with less porosity.
[0033] Example 4 The preparation method of the SiC-W2B5 / C composite material comprises the following steps: (1) 40.3 g of tungsten carbide (particle size 4±1 μm), 7.2 g of boron carbide (particle size 4±1 μm), 46.1 g of calcined petroleum coke (particle size 15±5 μm), 6.4 g of silicon powder (particle size 4±1 μm) and 100 mL of anhydrous ethanol were mixed and placed in a ball mill for ball milling at a ball-to-material ratio of 1:1 and a ball milling speed of 120 r / min for 18 h. After ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a raw material powder; (2) The raw material powder is placed in a graphite mold and hot-pressed in a sintering furnace for sintering at a temperature of 1500°C, a pressure of 20 MPa, and a time of 0.5 h. After sintering, the powder is cooled and taken out of the furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 15 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 10 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0034] Figure 7 This is the surface electron microscope image of the SiC-W2B5 / C composite material prepared in Example 4. Figure 7 It can be seen that when the content of W2B5 in the composite material is 15 vol.% and the content of SiC is 10 vol.%, the surface pores are further reduced. With the action of Si liquid phase sintering, the W2B5 particles are easier to move under the action of the liquid phase, filling the pores between the carbon phase layers, so that the carbon phase and the ceramic phase can be intertwined with each other to form a three-dimensional stacked layered structure, reducing the porosity inside the matrix.
[0035] Figure 8 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 4. Figure 8 It can be seen that the wetting effect between the carbon phase and the ceramic phase is better, which is more conducive to the interface bonding between the particles of the composite material, so that the interface bonding between the particles is good, the interface strength between the two phases is improved, the organizational structure of the composite material is more uniform and dense, and the comprehensive performance of the composite material is improved.
[0036] Example 5 The preparation method of the SiC-W2B5 / C composite material comprises the following steps: (1) 41.9 g of tungsten carbide (particle size 4±1 μm), 7.5 g of boron carbide (particle size 4±1 μm), 38.5 g of calcined petroleum coke (particle size 15±5 μm), 12.1 g of silicon powder (particle size 4±1 μm) and 150 mL of anhydrous ethanol were mixed and placed in a ball mill for ball milling at a ball-to-material ratio of 2:1 and a ball milling speed of 100 r / min for 24 h. After ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a raw material powder; (2) The raw material powder is placed in a graphite mold and hot-pressed in a sintering furnace for sintering at a temperature of 1500°C, a pressure of 15 MPa and a time of 1 h. After sintering, the powder is cooled and taken out of the furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 15 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 20 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0037] Fig. 9This is the surface electron microscope image of the SiC-W2B5 / C composite material prepared in Example 5. Fig. 9 It can be seen that when the content of W2B5 in the composite material is 15vol.%, and the content of SiC is 20vol.%, the composite materials are more closely bonded to each other. Due to the effect of liquid Si, the contact area between the material matrix particles is larger, which is conducive to filling the pores of the material. At the same time, the SiC ceramic phase particles can achieve the purpose of bonding, reduce the pores during the firing process, and improve the density of the composite material.
[0038] Fig.10 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 5. Fig.10 It can be seen that the ceramic phase generated by the reaction and the matrix carbon phase produce deflection displacement during the sintering process, which improves the interface bonding between the matrices and makes the carbon phases dense through diffusion, thereby improving the strength of the composite material.
[0039] Example 6 The preparation method of the SiC-W2B5 / C composite material comprises the following steps: (1) 40.6 g of tungsten carbide (particle size 4±1 μm), 7.2 g of boron carbide (particle size 4±1 μm), 34.6 g of calcined petroleum coke (particle size 15±5 μm), 17.6 g of silicon powder (particle size 4±1 μm) and 150 mL of anhydrous ethanol were mixed and placed in a ball mill for ball milling at a ball-to-material ratio of 2:1, a ball milling speed of 120 r / min, and a time of 12 h. After ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a raw material powder; (2) The raw material powder is placed in a graphite mold and hot-pressed in a sintering furnace for sintering. The temperature of the hot-pressing reaction sintering is 1500°C, the pressure is 10 MPa, and the time is 0.5 h. After the sintering is completed, the powder is cooled and taken out of the furnace to obtain a SiC-W2B5 / C composite material; wherein the content of W2B5 accounts for 15 vol.% of the total amount of the SiC-W2B5 / C composite material, and the content of SiC accounts for 30 vol.% of the total amount of the SiC-W2B5 / C composite material.
[0040] Fig.11 This is the surface electron microscope image of the SiC-W2B5 / C composite material prepared in Example 6. Fig.11 It can be seen that when the content of W2B5 is 15 vol.% and the content of SiC is 30 vol.%, the surface of the composite material is smooth, the structure is dense, the pores are few, the carbon phase layer is completely flat, the layers overlap each other, and the layers are stacked on each other. SiC and W2B5 particles are dispersed between the carbon phase layers, forming an embedded and embedded structure, filling the pores of the graphite matrix, and the sintering bonding between the C phase, SiC and W2B5 is good.
[0041] Fig.12 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Example 6. Fig.12 It can be seen that with the increase of SiC content, when the crack expands, dissociation will occur along the interface of the plate-like particles, causing the crack to deflect again. The extraction of particles prolongs the crack propagation path, increases the fracture energy, and has a toughening effect.
[0042] Comparative Example 1 The difference from Example 4 is that the silicon powder in the formula is replaced with 9.2g of silicon carbide powder (particle size 4±1μm, density 3.2g / cm 3 ), the amount of calcined petroleum coke is adjusted to 43.3 g, the temperature of hot pressing reaction sintering is 2000°C, the pressure is 30 MPa, the time is 1 h, and the rest is the same as Example 4.
[0043] Fig.13 The surface electron microscope image of the SiC-W2B5 / C composite material prepared in Comparative Example 1 is shown in FIG. Fig.13 It can be seen that when SiC powder is used instead of Si powder, and the content of W2B5 in the prepared composite material is 15 vol.%, and the content of SiC is 10 vol.%, there are more pores on the surface of the composite material because no liquid phase is generated during the sintering process.
[0044] Fig.14 This is a cross-sectional electron micrograph of the SiC-W2B5 / C composite material prepared in Comparative Example 1. Fig.14 It can be seen that the fracture surface of the composite material is relatively rough, mainly because the interface bonding between the ceramic phase and the carbon phase is weak, causing the carbon phase particles to slip and the fracture to occur between the particles.
[0045] Comparative Example 2 The difference from Example 3 is that the silicon powder is replaced with 14.2 g of Ti powder (particle size 4±1 μm) in the formula, and TiC (density 3.2 g / cm 3 ), the amount of tungsten carbide is adjusted to 38.5g, the amount of boron carbide is adjusted to 6.1g, the amount of calcined petroleum coke is adjusted to 41.2g, the temperature of hot pressing reaction sintering is 1800°C, the pressure is 30MPa, the time is 1h, and the others are the same as Example 3.
[0046] Fig.15 The surface electron microscope image of the TiC-W2B5 / C composite material prepared in Comparative Example 2 is shown in FIG. Fig.15It can be seen that when titanium powder is used instead of silicon powder, and the content of W2B5 in the prepared composite material is 10 vol.%, and the content of TiC is 10 vol.%, since Ti preferentially reacts with B in B4C during the reaction process, the B content in the reaction system is consumed, resulting in a lower content of W2B5. Therefore, the prepared composite material has poor density and more pores.
[0047] Fig.16 This is a cross-sectional electron micrograph of the TiC-W2B5 / C composite material prepared in Comparative Example 2. Fig.16 It can be seen that due to the low sintering activity, the interface bonding strength between the ceramic phase and the carbon phase particles is low, which makes it impossible for the surrounding particles to sinter together well, which leads to large cracks between the two phases, many holes in the cross section of the material, and poor sintering quality.
[0048] Comparative Example 3 The difference from Example 4 is that the silicon powder is replaced with 20.2 g of Mo powder (particle size 4±1 μm) in the formula, and MoC (density 9.1 g / cm 3 ), the amount of tungsten carbide is adjusted to 36.8g, the amount of boron carbide is adjusted to 6.6g, the amount of calcined petroleum coke is adjusted to 36.4g, the temperature of hot pressing reaction sintering is 2000℃, the pressure is 30MPa, the time is 1h, and the others are the same as Example 4.
[0049] Fig.17 The surface electron microscope image of the MoC-W2B5 / C composite material prepared in Comparative Example 3 is shown in FIG. Fig.17 It can be seen that when Mo powder is used instead of Si powder, and the content of W2B5 in the prepared composite material is 15 vol.%, and the content of MoC is 10 vol.%, it is also because Mo preferentially reacts with B in B4C during the reaction process, consuming the B content in the reaction system, so the prepared composite material has more pores.
[0050] Fig.18 This is a cross-sectional electron micrograph of the MoC-W2B5 / C composite material prepared in Comparative Example 3. Fig.18 It can be seen that due to the poor wettability of the ceramic phase and the carbon phase, the interface bonding strength of the composite material formed after hot pressing sintering is low, and it can be seen that the fracture is relatively rough.
[0051] Comparative Example 4 The difference from Example 5 is that the silicon powder is replaced with 32.5 g of MoSi2 powder (particle size 4±1 μm) in the formula, and MoC (density 9.1 g / cm 3 ) and SiC (density 3.2g / cm 3), the amount of tungsten carbide is adjusted to 37.5g, the amount of boron carbide is adjusted to 7.2g, the amount of calcined petroleum coke is adjusted to 22.8g, the temperature of hot pressing reaction sintering is 2000℃, the pressure is 30MPa, the time is 1h, and the others are the same as Example 5.
[0052] Fig.19 The surface electron microscope image of the MoC-SiC-W2B5 / C composite material prepared in Comparative Example 4 is shown in FIG. Fig.19 It can be seen that when molybdenum silicide powder is used instead of Si powder, the content of W2B5 in the prepared composite material is 15 vol.%, and the content of MoC and SiC is 20 vol.% in total. At this time, MoSi2 can also play the role of liquid phase, so the prepared composite material has fewer pores, but the effect is still not as good as silicon powder.
[0053] Fig. 20 This is a cross-sectional electron micrograph of the MoC-SiC-W2B5 / C composite material prepared in Comparative Example 4. Fig. 20 It can be seen that the particles at the fracture of the composite material remain intact, the internal structure is uniform and dense, and the crack propagation during the fracture process mainly occurs on the particle interface with weaker bonding. There are a large number of cleavage sections with blurred boundaries. A good interface bonding has been formed between the ceramic phase and the carbon phase. When fracture occurs, the cracks will preferentially extend along the carbon phase particles, thus exhibiting better bending strength.
[0054] Comparative Example 5 The difference from Example 6 is that silicon powder is not added to the formula, the amount of tungsten carbide is adjusted to 74.3g, the amount of boron carbide is adjusted to 13.4g, and the amount of calcined petroleum coke is adjusted to 7.4g. The content of W2B5 in the prepared composite material accounts for 45vol.% of the total amount of the composite material, the content of C phase accounts for 55vol.% of the total amount of the composite material, the temperature of hot pressing reaction sintering is 2000℃, the pressure is 30MPa, and the time is 1h. Others are the same as Example 6.
[0055] Fig.21 The surface electron microscope image of the W2B5 / C composite material prepared in Comparative Example 5 is shown in FIG. Fig.21 It can be seen that when the content of W2B5 in the composite material is 45 vol.%, the surface of the composite material is dense and has fewer pores.
[0056] Fig. 22 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Comparative Example 5. Figure 2It can be seen that the fracture surface of the composite material is relatively smooth, transgranular fracture occurs, and holes appear after the particles are pulled out. The ceramic phase content is high, so that the fracture mode of the composite material also has a small amount of transgranular fracture, forming a mixed crack propagation mode of transgranular fracture and intergranular fracture, which further improves the mechanical properties of the composite material.
[0057] The composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were subjected to performance tests, and the test methods were as follows: Density (g / cm 3 ): The Archimedes method of displacement was used to determine the volume density of the composite material. An analytical balance with an accuracy of 0.01 mg was used to determine the weight of the composite material in air and the floating weight in water. The density calculation formula is as follows: ; Where ρ is the bulk density of the composite material (g / cm 3 ), m1 is the weight of the dry composite sample in air (g), ρ1 is the density of water (g / cm 3 ), m2 is the weight of the sample after immersion in water (g).
[0058] Density (%): The ratio of the volume density of the composite material to the theoretical density. The calculation formula of the theoretical density is as follows: ; In the formula, ρ c is the theoretical density (g / cm 3 ), ρ i is the theoretical density of the i-th phase (g / cm 3 ), V i is the volume fraction of the ith phase (%).
[0059] Bending strength (MPa): Tested in accordance with GB / T 6569-2006; Fracture toughness (MPa·m 1 / 2 ): Tested in accordance with GB / T 23806-2009; Vickers hardness (GPa): Tested in accordance with GB / T 16534-2009; Graphitization degree (%): The interplanar spacing of the sample was measured by X-ray diffractometer, and the graphitization degree was calculated by the following formula: ; Where: g is the graphitization degree of the sample, d is 002 is the face distance.
[0060] The test results are shown in Table 1.
[0061] Table 1 Performance test results
[0062] As can be seen from Table 1, with the increase of W2B5 and SiC content, the performance of the SiC-W2B5 / C composite materials obtained in Examples 1 to 6 gradually increases. During the sintering process, SiC and W2B5 particles adhere to the surface of the carbon phase matrix, and are arranged as the carbon phase deflects and embedded between the layers. Under the continuous action of hot pressing pressure, the matrix carbon phase undergoes plastic flow deformation, and the internal large pores become small pores or even disappear. At the same time, SiC and W2B5 can also diffuse and rearrange under the action of sintering, filling up some residual pores inside the matrix.
[0063] In particular, with the addition of SiC, the liquid phase in the composite material sintering system promotes sintering, improves the sintering fluidity between particles, accelerates the migration and rearrangement of particles, and densifies the composite material matrix. With the increase of the proportion of Si components in the reaction system, the volume effect generated by the reaction of C and Si to form SiC also increases. In the sintering system, since Si is close to B and C in the periodic table and has similar properties, according to the principle of similar dissolution, Si is easily dissolved in B4C, thereby reducing the grain boundary energy of B4C and accelerating the decomposition of B4C. Liquid phase Si forms a solid solution with B and C, increasing the volume diffusion of powder particles. At the same time, the Si element will segregate on the B4C grain boundary, increase the surface energy of ceramic particles, and promote sintering densification. Therefore, with the increase of SiC content, the density of the material is greatly improved.
[0064] The composite effect of composite materials is reflected in their mechanical properties, which meet the law of mixture. The composition of the material is an important factor in determining the organization and performance. With the change of SiC content, the volume fraction of the ceramic phase and the C phase in the composite material changes, so its bending strength also changes accordingly. The addition of SiC fills the pores in the material matrix, reduces the porosity of the composite material, increases the effective bearing area of the force, and improves the bending strength of the composite material. The bending strength of ceramic materials is related to their porosity. The pores in ceramic materials are places where stress is concentrated. When the stress at the pores reaches a critical value, cracks will form and expand. Once the cracks begin to expand, they will spread rapidly until the material breaks. The reduction of porosity increases the effective cross-sectional area of the sample when it is subjected to external force, which increases the stress that the material can withstand, thereby improving its comprehensive performance.
[0065] By comparing Example 1 with Example 4, it can be seen that due to the different silicon carbide source materials, the performance of the composite materials is also different. In Example 1, SiC powder is directly added. Due to the high melting point of SiC powder, it does not promote sintering during the sintering process, resulting in poor interface bonding between the ceramic phase and the carbon phase of the composite material, low density, and poor performance.
[0066] By comparing Example 2 with Example 3, it can be seen that when Ti powder is selected to replace Si powder, although Ti can also promote sintering during the reaction process, Ti will preferentially react with B in B4C, consuming the B content in the reaction system and inhibiting the formation of W2B5, resulting in poor performance of the composite material.
[0067] By comparing Comparative Example 3 with Example 4, it can be seen that when Mo powder is selected to replace Si powder, Mo also reacts preferentially with B in B4C during the reaction process, resulting in poor performance of the composite material.
[0068] By comparing Example 4 with Example 5, it can be seen that when MoSi2 powder is selected to replace Si powder, MoSi2 can also promote sintering during the reaction process and promote the sintering of the composite material. However, due to the presence of the Mo element, it will still react preferentially with the B element, resulting in performance slightly lower than that of Example 5.
[0069] It can be seen from Comparative Example 5 and Example 6 that since no Si component is added in Comparative Example 5, the sintering temperature is high and the density of the prepared composite material is too large. At the same time, due to the poor interface bonding between the ceramic phase and the carbon phase in the composite material, the performance is slightly low.
[0070] The SiC-W2B5 / C composite material prepared by the present invention is introduced into the W2B5 / C composite material system by using the method of sintering SiC by Si powder reaction under the same ceramic phase ratio, and the Si powder plays a role of high-temperature liquid phase in the sintering system, accelerates the rearrangement of the reactant phase, promotes the dissolution and re-precipitation of the ceramic phase, and improves the densification of the composite material. The SiC generated by the reaction is located between the C phase and the W2B5 phase, and the interface strength of the composite material is improved. The prepared composite material has low density and high strength, and realizes that the performance advantage of the high carbon phase can still be maintained under low ceramic phase content, while reducing the sintering temperature and pressure, and on this basis, through material design and preparation technology, further optimization and improvement of performance are achieved, thereby expanding its application field.
Claims
1. A method for preparing a SiC-W2B5 / C composite material, characterized in that: The following steps are involved: (1) Mix tungsten carbide, boron carbide, calcined petroleum coke, silicon powder and ball milling dispersant, place in a ball mill for ball milling, dry and sieve after ball milling to obtain raw material powder; (2) The raw material powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace to obtain a SiC-W2B5 / C composite material; wherein the content of SiC accounts for 5-30 vol.% of the total amount of the SiC-W2B5 / C composite material.
2. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The content of W2B5 accounts for 5-15 vol.% of the total amount of SiC-W2B5 / C composite material.
3. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The molar ratio of the tungsten carbide, boron carbide, calcined petroleum coke and silicon powder is 1: (0.6-0.7): (10-70): (1-4).
4. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The particle sizes of the tungsten carbide and boron carbide are 3-5 μm, the particle size of the calcined petroleum coke is 10-20 μm, and the particle size of the silicon powder is 3-5 μm.
5. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The ball milling dispersant is anhydrous ethanol, and the ratio of the amount of the ball milling dispersant to the total amount of tungsten carbide, boron carbide, calcined petroleum coke and silicon powder is (100-150): 100 mL / g.
6. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The ball mill has a rotation speed of 80-120 r / min and a milling time of 12-24 h.
7. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The temperature of the hot pressing reaction sintering is 1500-1700°C and the pressure is 10-20MPa.
8. The method for preparing the SiC-W2B5 / C composite material according to claim 1, characterized in that: The hot pressing reaction sintering time is 0.5~1h.
9. A SiC-W2B5 / C composite material, characterized in that: The SiC-W2B5 / C composite material is prepared by the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Silicon carbide / tungsten boride composite material and preparation method thereof
CN103771859A
B4C-based double-layer ceramic composite material and preparation method thereof
CN112142473A
Preparation method of SiC composite ceramic material
CN115819090A
W2B5 / C composite material and preparation method thereof
CN118834069A
SiC complex sintered bodies and production thereof
EP0301802A2